Teacher as a Curriculum Developer and Mapper in a School Environment - Khorasgani, Amir Toghyani; Baratali, Maryam (IJRDO- Journal of Educational Research, 2019)
This paper studied viewpoints and experiences of instructors engaged in curriculum development and mapping regarding the activities and tasks that improve or prevent from efficient implementation of curriculum. For the aim of this study 6 instructors were elected from two schools. Classroom observations and semi-structured interviews conducted to collect data and information. Result supports previous studies and shows a considerable relationship between available procedure and desired procedure for curriculum development and mapping. Moreover, results emphasize some new and significant aspects which neglected or did not adequately discussed in previous studies. The following methods recognized for productive and prosperous curriculum development and mapping: integrated leadership, proper training, access to required resources, continuous communication about the innovations, and increasing motivations.